Hepatic failure, neonatal hemochromatosis and porto-pulmonary hypertension in a newborn with trisomy 21 - a case report - Poulik Janet; Bawle Erawati V; Joshi Aparna; Cortez Josef; Neil Erin; Zilberman Mark; El-Baba Mohammad F; Sood Beena G (BMC, 2010)
Abstract Liver failure in neonates is a rare but often fatal disease. Trisomy 21 is not usually associated with significant infantile liver disease. If present, hepatic dysfunction in an infant with Trisomy 21 is likely to be attributed to transient myeloproliferative disorder with hepatic infiltration by hematopoietic elements and may be associated with secondary hemosiderosis. A less commonly recognized cause of liver failure in neonates with Trisomy 21 is neonatal hemochromatosis (NH); this association has been reported in nine cases of Trisomy 21 in literature. NH is a rare, severe liver disease of intra-uterine onset that is characterized by neonatal liver failure and hepatic and extrahepatic iron accumulation that spares the reticuloendothelial system. NH is the most frequently recognized cause of liver failure in neonates and the commonest indication for neonatal liver transplantation. Although porto-pulmonary hypertension (PPH) has been reported as a complication of liver failure in adults and older children, this has not been reported in neonates with liver failure of any etiology. This is probably due to the rarity of liver failure in newborns, delayed diagnosis and high mortality. The importance of recognizing PPH is that it is reversible with liver transplantation but at the same time increases the risk of post-operative mortality. Therefore, early diagnosis of PPH is critical so that early intervention can improve the chances of successful liver transplantation. We report for the first time the association of liver failure with porto-pulmonary hypertension secondary to NH in an infant with Trisomy 21.